2009
DOI: 10.1039/b908299a
|View full text |Cite
|
Sign up to set email alerts
|

Single layer growth of sub-micron metal–organic framework crystals observed by in situ atomic force microscopy

Abstract: In situ atomic force microscopy was used to directly investigate the growth processes of the oriented metal-organic framework HKUST-1 grown on self-assembled monolayers on gold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 22 publications
6
50
0
2
Order By: Relevance
“…Careful cross-sectional analysis of single images of developing growth steps with 1.5 nm height suggests that the actual growth mechanism does not exclusively involve pre-formed paddle-wheel SBUs but is more likely to involve the simpler units such as individually solvated Cu 2+ and BTC 3-ions (BTC = benzene-1,3,5-tricarboxylate) ( Figure 3). It was established that the formation of the 1.5 nm high extended growth step occurs by a layer-by-layer mechanism [79]. According to this mechanism, each layer grows by initial attachment of BTC and copper species onto a stably terminated crystal surface A (Figure 3) to form a small volume of a d´2 22 step with metastable termination B.…”
Section: Crystal Surface Structurementioning
confidence: 99%
“…Careful cross-sectional analysis of single images of developing growth steps with 1.5 nm height suggests that the actual growth mechanism does not exclusively involve pre-formed paddle-wheel SBUs but is more likely to involve the simpler units such as individually solvated Cu 2+ and BTC 3-ions (BTC = benzene-1,3,5-tricarboxylate) ( Figure 3). It was established that the formation of the 1.5 nm high extended growth step occurs by a layer-by-layer mechanism [79]. According to this mechanism, each layer grows by initial attachment of BTC and copper species onto a stably terminated crystal surface A (Figure 3) to form a small volume of a d´2 22 step with metastable termination B.…”
Section: Crystal Surface Structurementioning
confidence: 99%
“…[11][12][13][14] In situ AFM studies of differing resolution have been reported for a number of MOFs, [15][16][17][18][19] revealing valuable information concerning their crystal growth and the growth of nanoporous materials.…”
Section: Introductionmentioning
confidence: 99%
“…The periodicity along the [100] direction (the growth direction perpendicular to the surface) of HKUST-1 is measured at 2.634 nm; each deposition cycle (one layer) with a thickness of half this value, 1.317 nm, corresponds to a half of the calculated periodicity along the [100] direction and thus verifies the half unit-cell growth. In situ AFM studies on HUKST-1 growth from solvothermal reaction also suggest an LBL mechanism [49]. It is noteworthy that the linear growth mode is established after 20 cycles.…”
Section: Thickness Roughness and Homogeneitymentioning
confidence: 96%
“…A wide range of technologies have been involved in this study such as extended X-ray absorption fine structure (EXAFS) spectroscopy, electrospray ionization mass spectroscopic (ESI-MS) [50], time-resolved in situ XRD study, atomic force microscopy (AFM) [51,52] and in situ time-resolved light scattering (TLS) [53]. Possibly, the most direct evidence for important growth species comes from in situ AFM studies [48,49] in which the LBL-based growth processes of oriented HKUST-1 crystals on SAM-modified gold substrates were investigated. These studies indicated a layer-by-layer mechanism of a constituent 1.5 nm d 111 crystal-spacing step of HKUST-1 and the influence of the step vertex on the rate of growth.…”
Section: Growth Mechanismsmentioning
confidence: 99%